The clustering of dusty star-forming galaxies: Connecting CMB cosmology and galaxy evolution - Addison, GE (2012)
In this thesis I construct various models to interpret measurements of the clustering of dusty star-forming galaxies through the angular power spectrum statistic. The goals of this work are, firstly, to facilitate the separation of the dusty galaxy contribution from the cosmic microwave background background (CMB) power spectrum, and, secondly, to improve our understanding of the physical properties of these galaxies. I present analysis of the first cross-correlation of millimeter and submillimeter sky maps, using data from the Atacama Cosmology Telescope (ACT) and the Balloon-borne Large-Aperture Submillimeter Telescope (BLAST), which revealed that the dusty galaxies that dominate the submillimeter sky are, to a significant extent, those same sources that are a nuisance contaminant for CMB cosmology. I then perform a joint fit to the ACT and BLAST power spectra as well as early results from the Planck Surveyor to construct a simple phenomenological template for the frequency and angular scale dependence of the contribution from clustered dusty galaxies to the total power spectrum. This template may be used to assist in extracting the CMB signal from future ACT and other data sets. The correlation between dusty galaxies and the thermal Sunyaev Zel'dovich effect leads to an additional contribution to the measured angular power spectrum that further hampers constraining quantities of cosmological interest. I present the first physically-motivated model for this correlation, and make predictions for its frequency and scale dependence as a CMB foreground. Finally, I combine angular power spectrum measurements from ACT, Planck and other instruments with deep far-infrared and submillimeter source number counts and constrain a model for the emission properties of these dusty galaxies. I demonstrate that the power spectrum carries significant constraining power and can improve our understanding of dust emission and star formation from unresolved objects at high redshift.